IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PAI KELAS VII SMPN SATU ATAP-2 TEWANG SANGALANG GARING - Pionera, Mutiarani; Syarif, Ahmad; Agustina, Sri Rahayu (Jurnal Hadratul Madaniyah, 2023)
This study aims to describe 1) the Implementation of Merdeka Belajar Curriculum (KMB) in PAI Subjects in Class VII of SMPN Satu Atap-2 Tewang Sangalang Garing and 2) the Supporting and inhibiting Factors for the Implementation of KMB in PAI Learning in Class VII of SMPN Satu Atap-2 Tewang Sangalang Garing. The research method used a descriptive qualitatif approach with data collection techniques including interviews, observation, and documentation. The results showed that: 1) Implementation of KMB in PAI Class VII SMPN Satu Atap-2 Tewang Sangalang Garing is carried out with the stages of planning, implementation and evaluation.. The planning stage includes the preparation of instruments related to the analysis of learning outcomes, the formulation of learning objectives, the flow of learning objectives, diagnostic assessments, and teaching modules. PAI teacher also planned a project to strengthen the Pancasila Student Profile by collaborating with other teachers to make adjustments to the project module provided by the Ministry of Education and Culture based on the needs of students, with the theme "Pelajar Berakhlak Mulia". At the implementation stage, the results of the planning instrument are applied in the beginning, core, and final activities of the PAI learning process. In the evaluation stage, the PAI teacher conducted a formative assessment of the effectiveness of KMB implementation in PAI learning; 2) Supporting Factors for the Implementation of KMB in Grade VII PAI Subjects are the motivation and guidance from the Principal who facilitates the teacher to participate in and hold training related to the Implementation of KMB. In addition, learning media such as Merdeka Curriculum textbooks, LCD projectors, Chromebooks, laptops and computers, and internet networks are provided. On the other hand, the inhibiting factors for the implementation of KMB in Grade VII PAI Subjects are that the teacher has not maximized the use of ICT and internet-based learning media